(3bjGS GdTeS hGdbeQ aj Yde Gdadc hGdfLhes - (3cjQcS Hf ajdhS GdHWQcs
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3agPG cJGH bjGS GdTeS ai Yde Gdadc hGdfLhe ddMcje Gdagje GddHjH cHQcS s
(3BNQgG (B:s
(3GdaQZ hgh eDQN GdOdh ef GdMhJ efRdg hai fSNI CNQi eGFi s
(3LeY GdeDda ajg MSGHGJ GdSfjf hGdCYhGe GdbHWi hMSGH Uhe GdfUGQi hMSGH eSjQ GdTeS hGdbeQ hGdCfhGQ GdJi Jchf ai cd TgQ hCYjGO GdbHW HMSGH eMces
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B83 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B111) s
Keywords: (3Gdadcs